Luminance and chromatic cues in a spatial integration task - HERNANDEZ-LLOREDA, Maria J; JANEZ, Luis (Vision research (Oxford), 2001)
These experiments explore the way in which cues provided by luminance and chromatic contrast interact in the spatial integration of elements. The stimuli were composed of bidimensional and isotropic Gauss functions. The elements were placed so that when experimentally manipulating the separations between the lines, subjects could generate an oriented percept from the elements sharing luminance or chromaticity. Results showed that, in most cases, grouping elements that share chromatic content is possible, in spite of variations in luminance content. Grouping elements as a function of luminance is more difficult when chromaticity alternates from one element to another. Lastly, if competing groupings are generated, the stimulus is structured as a function of chromatic content and not of luminance content.